The Spatial Model of Flood Risk in The Kanjiro River Basin North Luwu District, Indonesia - Hatta, Mukhsan Putra; Pongmanda, Silman; Suprapti, Ariningsih; Sari, Kartika; Rijal, Syamsu; Samad, Wasir; Fadlin, Fery (Engineering, Technology & Applied Science Research, 2025)
Flood risk mitigation in North Luwu Regency faces challenges due to the lack of detailed spatial data on the region’s complex topography. This limitation increases the potential for material and non-material losses. Accurate flood-prone area mapping requires reliable topographical and elevation data, which can be effectively obtained through Unmanned Aerial Vehicles (UAVs). The UAV technology enables high-resolution spatial data collection over large areas quickly and efficiently. This study integrates UAV surveys with terrestrial and hydrographic (bathymetric) measurements to develop a comprehensive flood risk spatial model. The objectives include the evaluation of the accuracy of the integrated rapid survey method and the design of a spatial model for flood risk reduction in the Kanjiro River Basin, North Luwu Regency. The study results include a high-resolution flood risk spatial model, structural and non-structural flood mitigation strategies, and a two-dimensional flood simulation using the HEC-RAS numerical model. The simulation assesses flood propagation, depth, and velocity, validated through primary data measurements. The findings provide a valuable tool for urban flood risk management and contribute to developing data-driven policies for flood mitigation.